Internalized weight bias is associated with perceived exertion and affect during exercise in a sample with higher body weight - KayLoni L. Olson; Stephanie P. Goldstein; Rena R. Wing; David M. Williams; Kathryn E. Demos; Jessica L. Unick (Wiley, 2021)
Abstract Objective For individuals with overweight/obesity, internalized weight bias (IWB) is linked to low physical activity (PA). This study used a laboratory‐based paradigm to test the hypothesis that IWB moderates the association between heart rate (HR) and perceived exertion and affect during PA. Methods Participants with overweight/obesity completed 30‐min of supervised moderate‐intensity treadmill walking (65%-75% of age‐predicted maximal HR). Body Mass Index (BMI) and Weight Bias Internalization Scale were assessed at baseline. HR was monitored every minute; perceived exertion and affect were assessed every 5 min. Linear mixed models were employed with random effects of time and participant. Results The sample (n = 59; 79.7% female, 91.5% white) had an average BMI = 32.1 kg/m2 (SD: 3.3), and age = 47.1 (SD: 10.3) years. There was a main effect of IWB on perceived exertion (greater IWB was associated with greater perceived exertion during exercise; p < 0.001). There was an interaction of IWB and HR on affect (B = −0.01, p < 0.01). For individuals with high IWB, HR elevations were associated with a negative affective response during exercise. For individuals with low IWB, HR elevations were associated with increased positive affect during PA. Conclusions Findings indicate that among individuals of higher body weight, IWB is associated with reporting higher perceived exertion during 30 min of moderate intensity PA. IWB moderated the relationship between increasing HR during exercise and affect. Among individuals with overweight/obesity who report IWB, the initial experience of PA may be harder and more unpleasant, with lasting implications for the adoption of PA.